Marketing Mix Factors for Service Business and Corporate Image Affecting the Decision to Use Road Freight Services - Teerapornlertratt, Preyaporn; Ayasanond, Chitpong; Munkongtum, Chutidaj (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: In an era where competition in the road freight transport service industry is challenging, understanding the marketing mix factors for service businesses and corporate image is essential to attract and retain customers. This research aims to analyze customer opinions and decision-making regarding these factors in the road freight transport business. The objectives of the study are 1) to examine the marketing mix factors for service businesses, corporate image, and decision-making in using road freight transport services, 2) to test the impact of the marketing mix factors for service businesses on decision-making in using road freight transport services, and 3) to test the impact of corporate image on decision-making in using road freight transport services. This research provides insights into factors influencing customer decision-making, crucial for developing marketing strategies and improving services in the road freight transport business. Methodology: This study focused on road freight transport service users in Thailand, selecting 180 participants using a specific random sampling method. A questionnaire was used to assess user opinions, with content validity (IOC=0.67) and reliability (Cronbach’s Alpha Coefficient=0.59) checked. Data collection concentrated on Bangkok and its vicinity, with sample proportions determined by transport activity density in each area to cover a wide range of businesses using road freight transport services. Descriptive statistics were used for general data and opinion analysis, and multiple regression analysis was employed to find statistically significant relationships between variables at the 0.05 level. Results: The study found that 1. The service process, marketing promotion, physical characteristics, and corporate image are the primary factors influencing customer decision-making. The corporate image was rated the highest, reflecting its importance in the overall perception and reputation of the corporation. 2. Most factors, such as products, price, location, marketing promotion, staff, and the service process, do not significantly impact the decision to use road freight services, except for the physical characteristics, which are the only factors significantly affecting the decision to use the service. 3. The corporate image does not significantly influence the decision to use road freight services. Conclusion: The research highlights the importance of service processes and physical characteristics in the road freight transport business. While corporate image plays a key role in creating customer satisfaction and decision-making, other elements of the service business marketing mix factors are less significant compared to physical characteristics in influencing service usage decisions.